Poly(caprolactone)/chitosan-based scaffold using freeze drying technique for bone tissue engineering application - Lor, Huai Chong (2015)
Highly porous 3Dimensional (3D) scaffold becomes a promising alternative approach for bone repairing. The aim of this research was to fabricate Polycaprolactone (PCL) blended with chitosan 3D-porous scaffold with improved hydrophilic behavior for bone tissue engineering applications. An effective technique, freeze drying technique was chosen to produce the sponge-like porous 3D scaffolds of 10%w/v pure PCL and 12%w/v blended PCL/Chitosan. Several characterizations such as Scanning Electron Microscope (SEM) and Attenuated Total Reflectance (ATR)-Fourier Transform Infrared (FTIR) were carried out to examine the morphologies and the chemical bonding of the scaffolds while water contact angle and water uptake experiment were done to investigate the hydrophilicity of the fabricated scaffolds. SEM observation revealed that the pure PCL and the blended PCL/Chitosan scaffolds had highly porous structure with average pore size of 73.6 μm and 74.9 μm which is in the optimum range of pore size for bone ingrowth. The results of ATR-FTIR showed that chitosan was successfully blended into PCL scaffold. The PCL/Chitosan blended scaffold fabricated in this study possessed homogeneous porous structures with improved hydrophilic properties. This PCL/Chitosan blended scaffold may have a high potential for the bone tissue engineering application.